Immunological Markers of Practically Healthy Persons Visual Analyzer State (London Journal of Medical and Health Research, 2025)
The eyes are a set of sensory organs that play a crucial role in the visual system [1]. Visual stimuli from our environment are processed by a complex system of interconnected neurons that begins with the optic nerve in the eye and extends to the visual processing center in the forebrain - the visual cortex [2].The eye is an extension of the brain and contains nerve tissue in the light-sensitive layer, the retina, which is related to brain tissue, and the outer membrane are an extension of the medulla [3]. The optic nerve has capillaries that have barrier properties due to the presence of dense interendothelial cell connections. In addition, the optic nerve has a well-developed, hemato-tissue barrier, which is formed by the pial vessels, the intermediate tissue of Kunt and the border tissue of Jacobi, located between the chorioidea and the optic disc (OD). All of these tissues are composed of astrocytes. However, the blood-tissue barrier has defects, which allows some substances, including antigens, to penetrate through it choriocapillary endothelial cells fenestrations also contribute to the penetration of various substances into the bloodstream [4, 5, 6].Most of the biological material is freely filtered through the tissue of the Jacobi tissue border and enters the optic nerve prelaminar region [3, 7, 8]. Thus, there is a circulation of certain substances from eyes certain compartments into the bloodstream and from the bloodstream into the eyes compartments, including the visual analyzer tissues. Consequently, the nervous tissues of the eye are not adequately protected from the body's innate immune system.The eye is one of several organs and tissues with immune privileges [9, 10]. The term immune privilege was introduced by Peter Medawar to show that the eye is exempt from the laws of transplantation immunology. Nevertheless, the impetus for the term came from the research of Dutch ophthalmologist van Doormal more than 150 years ago. In experiments on mice, he showed that the eyes anterior chamber protects allografts from rejection by the body's immune system [18]. Anterior chambers this feature was the impetus for the study eyes immune system and its interaction with the innate immune system [11, 12].Immune privilege is an active process in which certain tissues and the innate immune system cooperate to protect the eye from autoaggressive damage. The mechanisms that contribute to immune privilege include primarily tolerance of peripheral T-cells. Antigens entering the eye are taken up by local antigen-presenting cells, which migrate through the blood and initiate an immune response. This initiates the specific antibodies synthesis in the spleen [11, 13, 14] and specific T-cells are formed in the thymus. Most of them are eliminated under the target antigen influence expressed by the eye tissues itself, but some of them - gets back into the bloodstream and, accordingly, into the visual analyzer system [6, 9, 10].Thus, because of the visual analyzer tissues structure peculiarities, the eye antigens collide with the innate immune system. This encounter leads to the inevitable immune response development culminating in the specific immunoglobulins formation and sensitized lymphocytes that enter the bloodstream [11, 15, 16]. Consequently, there is a circulation not only of eye tissues antigens, but also of collision products with the innate immune system.In this regard, it is legitimate to assume that because of visual analyzer tissues structure some features, eye antigens certain amount encounters the innate immune system. As a result, immunoglobulins and leukocytes specifically sensitized to the eye tissues and, among them, to the visual analyzer tissues, inevitably appear in the circulation. Because immune responses are essential defense elements against foreignness and inflammation, the eye has developed distinct mechanisms that provide an immune response to avascular tissues' injury to the eye. It is now known that injury and/or pathology in the eyes avascular regions triggers an immune system response that culminates in fibrosis that impairs vision [17, 18, 19].Our early studies have shown that in the blood of practically healthy person (PHP), patients with glaucoma and keratitis circulates sensitized to the nerve, trabecular and lens tissues' antigens leukocytes. Their number clearly correlates with the pathology presence and its severity expression [20, 21, 22, 23, 24]. We explained this finding with the constantly occurring in almost all organs and tissues natural regeneration processes.Since primary open-angle glaucoma (POAG) belongs to neurodegenerative eye diseases [10, 25, 26], we investigated the PHP and POAG patients circulating leucocytes sensitization degree to optic nerve (ON) and optic disc (OD) tissue antigens. Moreover, the study results showed the presence in the PHP and POUG patients peripheral blood leukocytes specifically responding in vitro to ON and OD tissue antigens [23]. As a result, the question arose about the PHP peripheral blood leukocytes sensitization to other tissue antigens of the visual analyzer.
Keywords: Multiple Trauma; Accidents; Emergency Medicine.; secondary glaucoma; uveitis; posner-schlossman syndrome; intraocular pressure; topical corticosteroids.; plasma exchange; Vitamin B12; pernicious anemia; pseudo thrombotic microangiopathy; thrombocytopenic thrombotic purpura; knowledge; Adults; Practice; Nurse and IV fluid therapy